Teaching Ecological Responsibility in Islamic Religious Education: A QCA-Informed Reading of Q. 67:17 (al-Mulk) - Ali Murfi (MyResearch ID Publishing, 2025)
Purpose – This conceptual article reframes Q. 67:17 (al-Mulk) as a resource for Islamic religious education rather than only as an ecotheological interpretation. It asks how a Qur’anic threat narrative can be taught to cultivate ecological responsibility, religious literacy, and ecological leadership without reducing contemporary disasters to direct divine punishment. Methods/Design/Approach – This qualitative conceptual study applies Qualitative Content Analysis (QCA) to four tafsir: Ibn Kathir, al-Jalalayn, al-Wajiz by Wahbah al-Zuhaili, and the Indonesian Ministry of Religious Affairs’ tahlili tafsir. The resulting categories are synthesized with Islamic ecotheology, religious education, Islamic values education, and sustainability education literature to develop a pedagogical framework. Findings – The QCA identifies cross-tafsir categories of ḥāṣiban, false sense of security, social-moral conditions, warnings for individuals, communities, and rulers, and the rahmah-threat tension. The QCA-informed synthesis yields a three-layer model consisting of a textual-tafsiri layer, a normative ecotheological layer, and a pedagogical praxis layer. Originality/Value – The article contributes to religious education research by showing how Islamic scriptural interpretation can support ecological religious literacy, ethically bounded classroom reflection, and practical responsibility in Muslim educational settings. Practical Implications – The model can inform curriculum design, classroom inquiry, institutional culture, and ecological leadership by helping teachers, curriculum designers, and educational leaders connect Qur’anic learning with ecological responsibility while avoiding unsupported causal claims about particular disasters. Keywords Islamic religious education, ecological religious literacy, Q. 67:17, Qualitative Content Analysis, ecological leadership. Paper type Conceptual article